If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(x + 4) = 15 Reorder the terms: -9(4 + x) = 15 (4 * -9 + x * -9) = 15 (-36 + -9x) = 15 Solving -36 + -9x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -9x = 15 + 36 Combine like terms: -36 + 36 = 0 0 + -9x = 15 + 36 -9x = 15 + 36 Combine like terms: 15 + 36 = 51 -9x = 51 Divide each side by '-9'. x = -5.666666667 Simplifying x = -5.666666667
| S^2+4s-6=0 | | 5x+2=7x-5 | | 2c(c^3-3c^2-6c+18)=0 | | Z^3-(4i+4)z^2+(12i-2)z+8-4i=0 | | 4=a-6/3 | | 6x+i=3 | | 3(2x-1)=2(4x-4) | | X+90=4x-15 | | 6(x+7)=20 | | R=34x-(4x+180) | | Y=x+90+4x-15 | | .1x=12.5 | | 2w=1.44 | | 12/5n=2 | | 11(x+9)=14 | | 3-3.3= | | 2a^2-4a+1=0 | | A(2)+-3=5 | | x/y=3p/2t | | 8(x+9)=14 | | x^2+95x-3000=0 | | x^3-7x^2+14x-18=0 | | 3x+4-2x=36 | | 7x-15=10x+7 | | 24=5x+10-7x | | Fx=6/2x-3 | | 8x-23=3x-3 | | 4w+3=20-1w | | 16tgx=15cosx | | 5t^2+3=9t | | 1.3=m/4.3 | | y+9=-6 |